The Influence Of Accounting Information System Implementation, E-Commerce, Financial Literacy, And Access To Capital On MSME Performance - Ni Made Gresia Nurvita Dewi; I Ketut Suryanawa (SEAN Institute, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the driving wheels of the economy in Indonesia, so improving the performance of MSMEs must continue to ensure business sustainability. MSME performance can be used as one of the benchmarks for achieving company goals. This study aims to obtain empirical evidence of the influence of the application of accounting information systems, e-commerce, financial literacy and access to capital on the performance of MSMEs in Badung Regency. The sampling method used purposive sampling with a sample size of 100 MSMEs. Data collection was carried out by distributing questionnaires. The data collected was then analyzed using multiple linear regression analysis techniques. The results showed that the application of accounting information systems, e-commerce, financial literacy and access to capital had a positive and significant influence on the performance of MSMEs. The coefficient of determination is 0.914 which indicates that the ability of the independent variables to predict the dependent variable is 91.4%. 8.6% is influenced by other factors not examined in this research.